Juridical Analysis of Regional Regulation Formulation Techniques (Study of Title and Opening Framework in Sambas District Regulation Number 11 of 2015 concerning the Implementation of Legal Aid) - Tamrin Muchsin; Sardjana Orba Manullang; Saiful Rachman; Sri Sudono Saliro (Syiah Kuala Law Journal, 2020)
The authority of the regional government to regulate self-government affairs as stipulated in Article 10 paragraph (2) of Law Number 23 of 2014 concerning Regional Government and hierarchically is a juridical implementation of Article 18 paragraph (2) of the 1945 Constitution. Techniques for drafting statutory regulations, each Prevailing Law must refer to Law Number 12 of 2011 concerning the formation of statutory regulations. This paper will explain whether the framework for drafting the Sambas Regency Regional Regulation Number 11 of 2015 concerning the Implementation of Legal Aid is in accordance with Law Number 12 of 2011 concerning the Formation of Laws and Regulations. This research is a normative legal research which is defined as research on statutory rules which is viewed from the point of view of the legal hierarchy. The results show that the Preamble C (preamble) Framework and the legal framework are not in accordance with Law Number 12 of 2011 concerning the Formation of Laws and Regulations.